Building Your Data and People Manager Skills to Help Lead in MCBK. Issue 1 (14th October 2022) - Swain, Deborah; Cunningham, Christopher; Colbert‐Lewis, Danielle; Brown, Nijee; Tanner, William
ABSTRACT: Mobilizing Computable Biomedical Knowledge (MCBK) means establishing repositories of data and publications from open‐access sources that will support early reviews and faster validation of programs or software to improve healthcare. Supporting Learning Health Systems (LHSs) in the US and worldwide, developers, researchers, and healthcare practitioners aim for a learning system where knowledge‐generated processes in medical and clinical practices support continued care improvements. Thus, data and information need to be shared, and where possible, openly accessed and tested. Librarians and knowledge managers are the professionals who can lead these LHS efforts. Applying situated learning theory (Lave, 1991) in Alternative Event (AE), participants will interact in various ways aimed to promote leadership in LHS and CBK by information professionals and librarians. Building on knowledge from Michigan University School of Medicine's LHS leaders Charles Friedman and Rachel Richesson, there will be quick presentations on important aspects of MCBK and open access journals with activities. Participants review open access guidelines and samples from Learning Health Systems Journal Wiley Publication, and debate research quality for the use of data, machine learning, and/or computer software. Through role playing, attendees will learn how to persuade researchers to contribute data and publish in a reputable, open‐access electronic journal.